Respuesta :

Answer:

[tex](f-g)(x) =x^4-x^3-2x^2-4x+12[/tex]

Step-by-step explanation:

  • [tex]f(x) =x^4-4x^2+4[/tex] (Given)

  • [tex]g(x) =x^3-2x^2+4x-8[/tex] (Given)

  • [tex]\implies (f-g)(x) =(x^4-4x^2+4)-(x^3-2x^2+4x-8)[/tex]

  • [tex]\implies (f-g)(x) =x^4-4x^2+4-x^3+2x^2-4x+8[/tex]

  • [tex]\implies (f-g)(x) =x^4-x^3-4x^2+2x^2-4x+4+8[/tex]

  • [tex]\implies (f-g)(x) =x^4-x^3-2x^2-4x+12[/tex]

Answer:

  • (f - g)(x) = x⁴  - x³ - 2x² - 4x + 12

--------------------------

Given

Functions f an g

  • f(x) = x⁴ − 4x² + 4
  • g(x) = x³ − 2x² + 4x − 8

Find the composite function (f - g)(x)

  • (f - g)(x) =
  • f(x) - g(x) = x⁴ - 4x² + 4 - (x³ −-2x² + 4x - 8) =
  •                  x⁴ - 4x² + 4 - x³ + 2x² - 4x + 8 =
  •                  x⁴ - x³ - 2x² - 4x + 12